DESIGN ELEMENTS AND DESIGN PRINCIPLES IN THE JABUBOLON AT MEAT TOURISM VILLAGE, TOBA DISTRICT - Setiawan, Emily (Universitas Telkom, 2024)
The traditional architecture of Batak Toba is one of tourism attractions, tourismsector is oneof drivers of country's economy. The government's ef orts to enhance this sector with